Association Between Recycled Manure Solids Bedding and Subclinical Mastitis Incidence: A Canadian Cohort Study - Fréchette, Annie; Fecteau, Gilles; Côté, Caroline; Dufour, Simon (Frontiers in Veterinary Science, 2022)
Recycled manure solids (RMS) are increasingly used as bedding for dairy cows. However, potential impact of RMS bedding on animal health is not well described. The objective of this study was to evaluate subclinical mastitis incidence in cows housed on RMS bedding. Twenty RMS farms and a comparative group of 60 straw-bedded farms were enrolled in a one-year longitudinal study (2018-2019). Data from 11,031 dairy cows were collected. Variations of individual somatic cell count were evaluated using three different methods. First, we compared the cow’s mean lactation linear score between cows housed on the two bedding types. Then, we compared across bedding types the risk for a given cow of having a milk test with a linear score ≥ 4. Finally, we evaluated the dynamics of somatic cell count using pairs of tests within a cow. More specifically, we considered that only pairs of DHI tests where the first test yielded a linear score < 4 were at risk of an incident subclinical mastitis event. Then, we defined a newly acquired subclinical mastitis when the second test was ≥ 4. All models were adjusted for putative confounders. We could not highlight a significant association between bedding type and cow’s mean lactational linear score (least square mean of 2.47 in cows from RMS farms vs 2.37 in straw farms; 95%CI for linear score’s difference: -0.20, 0.40). Furthermore, we could not find an association between bedding type and the risk of a high linear score (≥ 4). For the latter, cows housed on RMS had 0.93 times the risk of having a high linear score than straw-bedded cows (%95CI: 0.68, 1.28). Moreover, cows on recycled manure solids farms had 0.73 time the risk of acquiring subclinical mastitis when compared to straw-bedded farms. Again, this risk was not statistically significant (%95CI: 0.54, 1.00). In our study, RMS bedding was not associated with subclinical mastitis, as measured by somatic cell count, when compared to cows housed on a more conventional bedding, straw bedding.